English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
1

How do you convert an equation from tan to cot?
For example, how would you convert

y = 4 tan(3x) into a cot equation in the format y = a cot(mx +b)

2006-12-21 10:30:32 · 6 answers · asked by odonata 2 in Science & Mathematics Mathematics

please help me with this Trig question...

2006-12-21 10:36:51 · update #1

Please explain your steps when u answer... =)

2006-12-21 10:38:27 · update #2

6 answers

It's true that tan(x) = 1/cot(x). However, it is also true that tan(x) = cot(pi/2 - x), because tangent is equal to the cotangent of the complement. In this case, we want to use the second relationship. So y = 4*tan(3x) = 4*cot(pi/2 - 3x) = 4*cot(-3x + pi/2). If you prefer to have a positive value for m, you could use the fact that cot(x) = -cot(-x), and say y - -4*cot(3x - pi/2).

Suppose you wanted to see what would happen if you used the first relationship instead. y = 4*tan(3x) ==> y/4 = tan(3x) ==> 4/y = cot(3x) ==> y = 4/cot(3x), which is not in the desired form, but is still an accurate expression, except that it might have points where it is undefined due to cotangent now being in the denominator.

2006-12-27 10:16:28 · answer #1 · answered by DavidK93 7 · 0 0

cot(x) = 1 / tan(x)

y = 4 tan(3x)
y = (1/4) cot(3x)

2006-12-21 10:38:06 · answer #2 · answered by Mike J 3 · 1 1

y = 4 tan(3x) = 4 * cot(pi/2 - 3x) = - 4 * cot(pi/2 + 3x)

2006-12-21 10:36:44 · answer #3 · answered by James Chan 4 · 0 2

tan = 1/cot

y 4/cot(3x)

2006-12-21 18:01:06 · answer #4 · answered by Renaud 3 · 0 2

y=4tan(3x)
=4 cot (270*+3x)

2006-12-21 11:15:15 · answer #5 · answered by raj 7 · 0 3

y=4tan3x
y=4cot(-3)x+(pi)/2

2006-12-21 11:42:16 · answer #6 · answered by ~Yalith~ 2 · 0 2

fedest.com, questions and answers